COVID-19 infection and vaccines: potential triggers of Herpesviridae reactivation - Alba Navarro-Bielsa; Tamara Gracia-Cazaña; Beatriz Aldea-Manrique; Isabel Abadías-Granado; Adrián Ballano; Isabel Bernad; Yolanda Gilaberte (Sociedade Brasileira de Dermatologia, 2023)
Abstract Since the onset of the COVID-19 outbreak, numerous articles have highlighted a possible link between COVID-19 vaccination or infection and Herpesviridae co-infection or reactivation. The authors conducted an exhaustive literature review on this topic, the results of which are presented individually for each member of the Herpesviridae family: Herpes Simplex Virus (HSV) types-1 (HSV-1) and 2 (HSV-2); Varicella-Zoster Virus (VZV); Epstein-Barr Virus (EBV); Cytomegalovirus (CMV); HHV-6; HHV-7; and HHV-8. These human herpesviruses can serve as prognostic markers for the COVID-19 infection and may even underlie some of the clinical manifestations initially attributed to SARS-CoV-2. In addition to SARS-CoV-2 infection, all corresponding vaccines approved to date in Europe appear capable of inducing herpesvirus reactivation. It is important to consider all viruses of the Herpesviridae family when managing patients infected with or recently vaccinated against COVID-19.